Translational neurodegeneration
"Translational Neurodegeneration is an open access, peer-reviewed journal that covers research, therapeutics and education for all aspects of neurodegenerative diseases. By offering a high-visibility forum for new insights and discussions, Translational Neurodegeneration creates a novel interface between the fields of basic, translational, and clinical research. It includes Parkinson's disease and movement disorders, Alzheimer's disease and other dementias, motor neuron disease and other neurodegenerative diseases."